2018
DOI: 10.1101/474098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stethoscope disinfection is rarely done in Ethiopia: what are the associated factors?

Abstract: 14Background: The stethoscope, which is universally used as a medical device by healthcare 15 providers, is likely to be contaminated by pathogenic microorganisms. And regular cleaning of 16 the diaphragm of the stethoscope with a suitable disinfectant is decisive. However, in the 17 resource constrained setting like many healthcare facilities in Ethiopia healthcare provider's 18 stethoscope disinfection practice and its associated factors have not been well studied so far. 19Therefore, this study sought… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In fact, the risk of contracting HAIs is variable and multifaceted: prevalently, it depends on a patient's immune status, the local prevalence of various pathogens, and the HCWs infection prevention practices. Hence, the need for having strong infection prevention programs nationally; and at the healthcare facility levels have been therefore important [29,30,32,43,44]. Un sustained compliance with infection prevention possibly places HCWs at equal, if not at higher risk of contracting bacterial and viral infections such as HIV, HBV, HCV, and MRSA in healthcare facilities [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the risk of contracting HAIs is variable and multifaceted: prevalently, it depends on a patient's immune status, the local prevalence of various pathogens, and the HCWs infection prevention practices. Hence, the need for having strong infection prevention programs nationally; and at the healthcare facility levels have been therefore important [29,30,32,43,44]. Un sustained compliance with infection prevention possibly places HCWs at equal, if not at higher risk of contracting bacterial and viral infections such as HIV, HBV, HCV, and MRSA in healthcare facilities [9].…”
Section: Discussionmentioning
confidence: 99%
“…From that day on, considerable progress has been made in understanding the basic principles, acceptance, and use of evidence-based infection prevention practices in Ethiopia [9]. Despite the effort underway, studies reported inconsistent findings regarding HCWs infection prevention practice in Ethiopia [19,20,27,29-33]. Although the reporting of such practices is important for the prevention and control of HAIs and improving quality of care, the previously conducted studies had many differences in the geographical regions and preceded remarkable variations in the reported practices.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was determined using Epi Info™ 7.1.1.14 statistical software (Center for Disease Control and Prevention, 2013) using single population proportion formula with the assumption of 95% confidence level, 5% precision, considering the proportion of healthcare workers who had safe stethoscope disinfection practice was 39.7% [2], and considering 25% non-response rate. The calculated sample size was (n=460).…”
Section: Methodsmentioning
confidence: 99%
“…Stethoscopes are the most customary medical equipment wield by physicians on a daily basis, among various patients. With the rise of potential infections in the healthcare setups, stethoscope disinfection should not be pardoned [1][2][3][4]. The Gold Standard is to disinfect stethoscopes after each contact with patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation